The Moderating Role of Human Resource Competence in The Relationship Between Digital Literacy, Marketing Innovation, and MSMEs Business Performance in Pontianak - Arninda Arninda; Ferdy Firmansyah; Ryanti Ryanti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of digital literacy and marketing innovation on MSME business performance in Pontianak, with human resource competence as a moderating variable. The study employed a quantitative approach using a survey method involving 200 food and beverage MSMEs in Pontianak selected through purposive sampling. Data were analyzed using Moderated Regression Analysis (MRA) with SPSS 23. The findings reveal that digital literacy has a positive and significant effect on MSME business performance (B = 0.098; p < 0.05), while marketing innovation demonstrates the strongest influence on business performance (B = 0.421; p < 0.001). Furthermore, human resource competence significantly moderates the relationship between digital literacy, marketing innovation, and MSME business performance. The coefficient of determination (R² = 0.611) indicates that 61.1% of MSME business performance can be explained by the variables examined in this study. These findings imply that strengthening digital capability, marketing innovation, and human resource competence is essential for improving MSME competitiveness and sustainability in the digital era.